Analisis Karakter Manusia Munafik Melalui Pendekatan Tematik Digital Quran - Nur Rohmatul Azka; Udin Supriadi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2020)
Hypocritical people are basically those who disobey God, and His Apostle, even though they are born believers. In another view, hypocrisy is interpreted as a two-faced attitude and appears differently from the circumstances it craves. In the hadith it is mentioned that the sign of a hypocrite is threefold: When he speaks lying, when he rains down he disavows, and When he is believed he betrays. Then how is the hypocritical human nature mentioned in the Quran. The author uses the quran's digital thematic approach to find verses related to hypocritical human characters. The most fundamental feature of hypocritical man is his concern between faith and disbelief and his ability to make a firm and clear attitude with regard to the beliefs of tawhid. This is because he is a person who lacks confidence. They cannot make a firm and clear decision to join the believers or with the musyrikins.